Experimental investigation on masonry structural joint repointing with cement-polymer mortar and polypropylene strips - Sergey Churilov; Elena Dumova-Jovanoska; Veronika Shendova; Lidija Krstevska; Bojan Damchevski; Dime Janchev (Građevinar)
Unreinforced masonry structures are prevalent in urban areas. Many of these structures are vulnerable to earthquakes, which are the primary causes of damage and failure. Therefore, conducting comprehensive studies to assess the structural capacity of these buildings is crucial for understanding their behaviour and vulnerability and for proposing effective strengthening measures. This integrated experimental and numerical study explored the effectiveness of joint repointing as a viable method for strengthening masonry structures. A review of recent research on various joint repointing techniques and materials is presented in the first part of this paper. The experimental investigations of unreinforced and strengthened masonry panels, utilising cement-polymer mortar and polypropylene strips in bed joints subjected to compressive and diagonal compressive strengths, are detailed. The experimental results demonstrate that structural joint repointing significantly improves the strength and has a minor effect on the ductility of the masonry, particularly when the original mortar has low-strength properties, as expected in existing buildings. The obtained results enable the calibration of nonlinear numerical models and modelling strategies used to study the elements in a more extensive manner, allowing for parametric studies and the application of the findings to existing buildings.